Numerical Simulation of the Influence of CO2 on the Combustion Characteristics and NOX of Biogas - Ma, Jinshuang; Qi, Chuanjia; Luo, Siyi; Zuo, Zongliang (Frontiers in Energy Research, 2022)
The existence of inert gases such as N2 and CO2 in biogas will reduce the proportion of combustible components in syngas and affect the combustion and NOx formation characteristics. In this study, ANSYS CHEMKIN-PRO software combined with GRI-MECH 3.0 mechanism was used to numerically simulate the effects of different CO2 concentrations (CO2 volume ratio in biogas is 0 41.6%) on flame combustion temperature, flame propagation speed and nitrogen oxide formation of complex biogas with low calorific value. The results showed that when the combustion reaches the chemical equilibrium, the flame combustion temperature and flame propagation speed decrease with the increase of CO2 concentration, and the flame propagation speed decreases even more slowly. Meanwhile, the molar fraction of NO at chemical equilibrium decreases with the increase of CO2 concentration and the decrease is decreasing, which indicates that the effect of CO2 concentration in biogas on NO is simpler. While the molar fraction of NO2 does not change regularly with the change of CO2 concentration, the effect of CO2 concentration in biogas on NO2 is complicated. The highest molar fraction of NO2 was found at chemical equilibrium when the CO2 concentration was 33.6%, when the target was a typical low calorific value biogas.